European Stroke Organization guideline for the diagnosis and treatment of cerebral venous thrombosis – endorsed by the European Academy of Neurology. (20th August 2017) - Ferro, J. M.; Bousser, M.‐G.; Canhão, P.; Coutinho, J. M.; Crassard, I.; Dentali, F.; di Minno, M.; Maino, A.; Martinelli, I.; Masuhr, F.; Aguiar de Sousa, D.; Stam, J.; et al.
Abstract : Background and purpose: Current guidelines on cerebral venous thrombosis (CVT) diagnosis and management were issued by the European Federation of Neurological Societies in 2010. We aimed to update the previous European Federation of Neurological Societies guidelines using a clearer and evidence‐based methodology. Method: We followed the Grading of Recommendations, Assessment, Development and Evaluation system, formulating relevant diagnostic and treatment questions, performing systematic reviews and writing recommendations based on the quality of available scientific evidence. Results: We suggest using magnetic resonance or computed tomographic angiography for confirming the diagnosis of CVT and not routinely screening patients with CVT for thrombophilia or cancer. We recommend parenteral anticoagulation in acute CVT and decompressive surgery to prevent death due to brain herniation. We suggest preferentially using low‐molecular‐weight heparin in the acute phase and not direct oral anticoagulants. We suggest not using steroids and acetazolamide to reduce death or dependency. We suggest using antiepileptics in patients with an early seizure and supratentorial lesions to prevent further early seizures. We could not make recommendations concerning duration of anticoagulation after the acute phase, thrombolysis and/or thrombectomy, therapeutic lumbar puncture, and prevention of remote seizures with antiepileptic drugs. We suggest that, in women who have suffered a previous CVT, contraceptives containing oestrogens should be avoided. We suggest that subsequent pregnancies are safe, but use of prophylactic low‐molecular‐weight heparin should be considered throughout pregnancy and puerperium. Conclusions: Multicentre observational and experimental studies are needed to increase the level of evidence supporting recommendations on the diagnosis and management of CVT. Abstract : Click here for the corresponding questions to this CME article.